Phase portrait of control movements – one of the criteria of technical skill of an athlete - Zagrevskiy V.I.; Zagrevskiy O.I.; Lavshuk D.A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to develop an integral criterion of an athlete’s technical skill and a computer application for constructing a phase portrait of sports exercises. Methods and structure of the study. The research instrumental base is video materials of gymnastic exercises, computer tools for processing research results using the MatLab software environment. Performer: A. Bergovin, Master of Sports in artistic gymnastics, Republic of Belarus. Two revolutions were performed in a row, which were compared with each other based on phase portraits. Results and conclusions. It was revealed that the deformation of the kinematic control structure is most significant in changing the area of ​​the phase portrait and varies within 15-30% of the area of ​​the original image, which, however, does not lead to a significant restructuring of the technical basis of the motor action and makes it possible to implement the target setting of the exercise. Amplitude changes in executive function are less significant in solving a motor task than the rate of change in the joint angle. A comprehensive «Kinematic Control» functionality has been developed, which allows for an integral assessment of the athletes technical skill.